A feasibility study on ambidextrous armchairs - Barrera, Christian T.; Nimo, John Saleem T.; Panis, Ramon Miguel C.; Tandog, Anne Klarisse H.
Recent studies show that 10% of the world's population is left-handed. This follows that most products, tools and equipment are designed biased for right-handed. Due to this, the left-handed community population has experienced injuries such as back pains, shoulder pains and, in rare cases, death. Filipino students spend at least 14 years of their lives in school; 6 of these years in elementary school, the next 4 in secondary school and the remaining in the college level. A significant number of schools in the Philippines employ the use of armchairs for their students. There are schools who have left-handed armchairs; however, the number of these chairs is minimal and most of the time not enough for the population. An opportunity was seen by the group: an armchair that will be able to meet the needs of both the right-handed and left-handed populations. Thus, Dexter was created. Dexter is an ambidextrous armchair that makes use of a rotating arm mechanism, allowing the chair to be transformed from a right-handed armchair to a left-handed one conveniently. This gives the user, whether right-handed or left-handed, comfort while using the chair. It also gives schools the advantage of being able to serve the entire student population. Dexter will mainly be sold to private primary and elementary schools in the National Capital Region. It will be introduced to the market by direct pitching to the schools and by portals for promotion emphasizing health and safety. The ambidextrous armchair will be available in forms: fiberglass and plastic. Both types will use metal for the rotating arm mechanism. The main manufacturing plant of Dexter will be located in Araneta Avenue in Cubao, Quezon City as it has sufficient lot spaces, lower costs and is near to the intended market. The company will cover the secondary manufacturing and the distribution part of the supply chain. They will assemble the product, with the main chair and the arm outsourced from other manufacturers. The initial investment cost for Dexter will be at 12.201 Million Pesos, 70% of this cost will be loaned from the bank with an average interest of 7.75% and the remaining 30% will come from investments. With its financial projections, that company is expected to be profitable by the third year of business after recovering all costs incurred during the start up. The company is expected to be liquid all throughout the five years of its implementation. We also see that the company becomes more efficient in utilizing its assets as there is an increase in the asset turnover ratio. After analyzing the investment evaluations, the project is deemed to be feasible and profitable as it has a high IRR and a positive net-present value. The socio-economic impact of the business is highly dependent on how the company tries to link itself to its community. By immersing itself to the society it intends to operate within with, Dexter was able to understand what the concerns and needs of the stakeholders are. The effects of establishment of the business were classified as social, economic, and environmental. For each facet, issues and concerns arose, posing threats to the business. Knowing the impact of these factors, Dexter formulated and laid out actions that the company will employ prior to and during its operations. The venture intends to be a responsible business, mindful of its duties and obligations to the society, economy, and the environment. It created a cause, elevating and pushing forward equality and environmental awareness, with the hope of transforming the community around it to be responsible citizens as well. Dexter hopes to develop the economic sector of Quezon City as it invites business to its agglomerate and develop partnerships with existing ventures in the city. The new business is also a new opportunity for people looking for work, eventually decreasing the unemployed citizens of the country. With the contributions of Dexter outweighing the costs of establishing it, it can be concluded that venturing into the business is socio-economically feasible.